On impatience, education, returns, and inequality - Guimarães, Guido Couto Penino (2015)
In this paper we investiga te the impact of initial wealth anel impatience heterogeneities, as wcll as differential access to financia! markets on povcrty anel inequality, anel cvaluate some mechanisms that could be used to alleviate situations in which these two issues are alarming. To address our qucstion we develop a dynamic stochastic general cquilibrium modo! of educational anel savings choicc with heterogeneous agents, where individuais differ in their initial wealth anel in their discount factor. We find that, in the long run, more patient households tend to be wealthier anel more educated. However, our baseline model is not able to give as much skewness to our income distribution as it is rcquircd. We then propose a novel returns structure based on empírica! observation of heterogeneous returns to different portfolios. This modification solves our previous problem, evidencing the importance of the changes made in explaining the existing levels of inequality. Finally, we introducc two kinds of cash transfers programs- one in which receiving thc benefit is conditional on educating the household's youngster (CCTS) anel one frec of conditionalities (CTS) - in order to evaluate the impact of these programs on the variables of concern1 Wc fine! that both policies have similar qualitativo rcsults. Quantitatively, howcvcr, the CCTS outperforms its unconclitional version in all fielcls analyzecl, revealing itself to be a preferable policy.